2020
DOI: 10.1016/j.soildyn.2020.106160
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a generalized nonlinear multi-span bridge system subject to multi-support excitation using a Bouc-Wen hysteretic model

Abstract: This paper presents a generalized reduced-order nonlinear model subjected to multi-support seismic excitation. The hysteretic, nonlinear, relationship of piers is phenomenologically captured by a calibrated Bouc-Wen model. This generalized reduced-order model is benchmarked against legacy physical experimental tests performed at the University of Bristol.A deterministic approach using real spatiotemporal ground motions recorded at the SMART-1 array, Taiwan, is employed as an alternative to a stochastic methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…They proved that the new method increases the estimation accuracy in terms of the constraint effect of respected parameters. Meibodi and Alexander (2020) [5] use the Bouc-Wen model to capture the hysteretic nonlinear relationship of piers of a multi-span bridge subjected to seismic excitation. They showed that the computational efficiency of the modelling of the multi-span bridge greatly improved as compared to typical finite element analysis (FEA) by introducing the Bouc-Wen element within the model.…”
Section: Bouc-wen Hysteresis Modelmentioning
confidence: 99%
“…They proved that the new method increases the estimation accuracy in terms of the constraint effect of respected parameters. Meibodi and Alexander (2020) [5] use the Bouc-Wen model to capture the hysteretic nonlinear relationship of piers of a multi-span bridge subjected to seismic excitation. They showed that the computational efficiency of the modelling of the multi-span bridge greatly improved as compared to typical finite element analysis (FEA) by introducing the Bouc-Wen element within the model.…”
Section: Bouc-wen Hysteresis Modelmentioning
confidence: 99%
“…Both near-fault and far-fault ensembles are used as input. The non-dimensionalized hysteretic Bouc-Wen model ( [36], [37], [38]) is used to model the inelastic behaviour of SDOF structures:…”
Section: Comparison Of Inelastic Response Spectramentioning
confidence: 99%